Original articleA spatial pattern analysis of β-amyloid (Aβ) deposition in the temporal lobe in Alzheimer\'s disease - Armstrong, Richard A. (Folia Neuropathologica, 2010)
To determine the factors influencing the distribution of -amyloid (Aβ) deposits in Alzheimer’s disease (AD), the spatial patterns of the diffuse, primitive, and classic A deposits were studied from the superior temporal gyrus (STG) to sector CA4 of the hippocampus in six sporadic cases of the disease. In cortical gyri and in the CA sectors of the hippocampus, the Aβ deposits were distributed either in clusters 200-6400 µm in diameter that were regularly distri-buted parallel to the tissue boundary or in larger clusters greater than 6400 µm in diameter. In some regions, smaller clusters of Aβ deposits were aggregated into larger ‘superclusters’. In many cortical gyri, the density of Aβ deposits was positively correlated with distance below the gyral crest. In the majority of regions, clusters of the diffuse, primi-tive, and classic deposits were not spatially correlated with each other. In two cases, double immunolabelled to reveal the Aβ deposits and blood vessels, the classic Aβ deposits were clustered around the larger diameter vessels. These results suggest a complex pattern of Aβ deposition in the temporal lobe in sporadic AD. A regular distribution of Aβ deposit clusters may reflect the degeneration of specific cortico-cortical and cortico-hippocampal pathways and the influence of the cerebral blood vessels. Large-scale clustering may reflect the aggregation of deposits in the depths of the sulci and the coalescence of smaller clusters.